Negotiating in the skies of Hong Kong: The efficacy of the Behavioral Influence Stairway Model (BISM) in suicidal crisis situations - Vecchi, Gregory M.; Wong, Gilbert K.H.; Wong, Paul W.C.; Markey, Mary Ann (Aggression and violent behavior, 2019)
Law enforcement agencies often deal with difficult, dangerous, and disordered individuals by applying the theory and practice of tactical negotiation, which is composed of a unique application of communication techniques aimed at obtaining voluntary compliance. Known as hostage or crisis negotiation, law enforcement tactical negotiation (LETN) has shown to be an effective technique for resolving barricaded hostage and crisis situations, kidnappings, and suicidal incidents. Over the years, there have been several models of LETN, however; most of them are based on the assumption that the 1) subject is rational and 2) the subject views the officer as credible; however, in situations where people are in crisis, emotions control their actions rather than reason. Therefore, being successful requires the officer to return the subject to a rational state of mind and establish trust (credibility). If either of these, elements are missing, then traditional negotiation will most likely fail in gaining voluntary compliance in a timely manner. This is especially true with suicidal persons who have exceeded their ability to cope with their situation and believe that no one will help them. The Behavioral Influence Stairway Model (BISM) operates on the premise that a state of personal crisis occurs when coping and social support mechanisms fail and that to end the crisis, at least one of these elements must be restored. In these situations, the BISM provides a method by which the officer can re-establish social support through effectively dealing with emotions (thus returning the individual to a rational state of mind) and demonstrating empathy (thus obtaining trust). In Hong Kong, the Police Negotiation Cadre (PNC) routinely deals with a unique form of suicide where persons in crisis frequently choose jumping off high-rise buildings as their preferred means of suicide. Unlike in the United States, where a significant number of suicides involve barricaded individuals with firearms, most LETN in Hong Kong is accomplished face-to-face, since officer safety relating to firearms is atypical. Despite these differences in structure, culture, and language, the BISM is routinely used to successfully resolve suicidal situations in Hong Kong, based on the theory that emotions and relationship needs are universal and not contingent on context. Therefore, this article will present an updated version of the BISM and extend the principles of the BISM cross-culturally by providing evidence of its efficacy in negotiating with suicidal persons who threaten to jump from multi-story buildings in Hong Kong, as well as its proactive application to non-police intervenors.